1986
DOI: 10.1111/j.1945-5100.1986.tb01223.x
|View full text |Cite
|
Sign up to set email alerts
|

Gallium‐bearing Sphalerite in a Metal‐sulfide Nodule of the Qingzhen (Eh3) Chondrite

Abstract: The Qingzhen (EH3) chondrite contains a population ofspheroidal metal-sulfide nodules, which display textural evidence of reheating and melting. Evidence of metal sulfuration is also present, suggesting replacement of metal by sulfide during melting. This process has led to the nucleation of perryite along metal-sulfide interfaces.Gallium-bearing sphalerite and a Cu-sulfide of composition intermediate between chalcopyrite and cubanite occur as inclusions within the metal of some nodules. Other phases present a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 12 publications
3
16
0
1
Order By: Relevance
“…Gallium concentrations tend to be higher in low-temperature, carbonate-hosted replacement deposits. Moskalyk (2003) states that Zn ores from some Mississippi Valley type deposits in the USA contain 50 ppm Ga. Melcher et al (2006) compiled data for Ga concentrations in sphalerite from a number of Namibian Pb-Zn deposits, indicating concentrations at the several hundreds of ppm level in the main sphalerite generation at Khusib Springs and 2000-3120 ppm in very low-Fe-sphalerite from the Tsumeb ore. Rambaldi et al (1986) report concentrations of 2.1-3.7 wt.% Ga in sphalerite from a sulfide nodule within a chondrite, concordant with the high solubility and complete solid solution determined experimentally at elevated temperatures (Krämer et al, 1987;Ueno and Scott, 1991).…”
Section: Element Trendssupporting
confidence: 62%
“…Gallium concentrations tend to be higher in low-temperature, carbonate-hosted replacement deposits. Moskalyk (2003) states that Zn ores from some Mississippi Valley type deposits in the USA contain 50 ppm Ga. Melcher et al (2006) compiled data for Ga concentrations in sphalerite from a number of Namibian Pb-Zn deposits, indicating concentrations at the several hundreds of ppm level in the main sphalerite generation at Khusib Springs and 2000-3120 ppm in very low-Fe-sphalerite from the Tsumeb ore. Rambaldi et al (1986) report concentrations of 2.1-3.7 wt.% Ga in sphalerite from a sulfide nodule within a chondrite, concordant with the high solubility and complete solid solution determined experimentally at elevated temperatures (Krämer et al, 1987;Ueno and Scott, 1991).…”
Section: Element Trendssupporting
confidence: 62%
“…Figure 8 summarizes data on the chemical compositions of known (Fe,Zn,Mn)S minerals, both of meteoritic and terrestrial origin. Besides Indarch, Fe-dominant members of FeS-ZnS-MnS solid solutions were found in 11 meteorites related to enstatite chondrites: Yilmia (EL6) (Buseck and Holdsworth 1972); Pillistfer (EL6), ALHA77295 (EH3) (Kissin 1989); MAC88136 (EL3) (Lin et al 1991); LEW88135 (EL6), MAC88180 (EL3), MAC88184 (EL3) (Zhang and Sears 1996); Yamato-86004 (EH6) (Lin and Kimura 1997); PCA91020 (EL3) (Petrichenko and Ulyanov 1998); Qingzhen (EH3) (Rambaldi et al 1986;El Goresy et al 1988;El Goresy and Ehlers 1989;Kissin 1989;Lin and El Goresy 2002); and Yamato-691 (EH3) (El Goresy et al 1988;Kimura 1988;Ikeda 1989). Other extraterrestrial occurrences include three iron meteorites (octahedrites) related to the IAB chemical group: Odessa (El Goresy 1967), Waterville (Weinke et al 1977), and Burkhala (Yaroshevsky et al 1989).…”
Section: Crystal Structure and Crystallographymentioning
confidence: 97%
“…Paul Ramdohr (Ramdohr 1963(Ramdohr , 1973 was the first who optically characterized (Fe,Zn)S sulfide (Mineral K) in the Indarch meteorite (enstatite chondrite, EH4). Further investigations revealed that Fe-dominant members of (Fe,Zn,Mn)S solid solutions are typical accessory minerals in enstatite chondrites (Buseck and Holdsworth 1972;Kissin 1986Kissin , 1989Rambaldi et al 1986;El Goresy andEhlers 1987, 1989;El Goresy et al 1988;Kimura 1988;Ikeda 1989;Lin et al 1991;Zhang and Sears 1996;Kimura 1997, 1998;Petrichenko and Ulyanov 1998;Lin and El Goresy 2002;Lorenz et al 2003). These minerals were also described from three iron meteorites (octahedrites) related to the IAB group: Odessa, Waterville and Burkhala (El Goresy 1967;Weinke et al 1977;Yaroshevsky et al 1989).…”
Section: Introductionmentioning
confidence: 94%
“…The spheroidal metal‐sulfide nodules in highly unequilibrated EH3s such as Sahara 97072 (Fig. 1) and Qingzhen were proposed to be pre‐accretionary nebular objects that experienced condensation/evaporation and transient nebular melting events as well as several later metamorphic episodes (Rambaldi et al. 1986; El Goresy et al.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that some perryite inclusions not appearing to be associated with sulfides actually are when the third dimension of thin sections is considered. The kamacite‐perryite‐troilite assemblage was interpreted to be a product of sulfidation of Fe‐Ni alloy (Rambaldi et al. 1986; Lin and El Goresy 2002).…”
Section: Introductionmentioning
confidence: 99%